Elite Swimmers’ Training Patterns in the 25 Weeks Prior to Their Season’s Best Performances: Insights Into Periodization From a 20-Years Cohort - Hellard, Philippe; Avalos-Fernandes, Marta; Lefort, Gaelle; Pla, Robin; Mujika, Inigo; Toussaint, Jean-François; Pyne, David B. (Frontiers in Physiology, 2019)
Background: This study investigated the periodization of elite swimmers’ training over the 25 weeks preceding the major competition of the season. Methods: We conducted a retrospective observational study of elite male (n = 60) and female (n = 67) swimmers (46 sprint, 81 middle-distance) over 20 competitive seasons (1992-2012). The following variables were monitored: training corresponding to blood lactate <2 mmol.L-1, 2 to ≤4 mmol.L-1, >4‒6 mmol.L-1, >6 mmol.L-1, and maximal swimming speed; general conditioning and maximal strength training hours; total training load (TTL); and the mean normalised volumes for both in-water and dryland workouts. Latent class mixed modelling was used to identify various TTL pattern groups. The associations between pattern groups and sex, age, competition event, Olympic quadrennial year, training contents, and relative performance were quantified. Results: For the entire cohort, ~86‒90% of the training was swum at an intensity of [La]b ≤4 mmol.L-1. This training volume was divided into 40‒44% at <2 mmol.L-1 and 44‒46% at 2 to ≤4 mmol.L-1, leaving 6‒9.5% at >4‒6 mmol.L-1 and 3.5‒4.5% at >6 mmol.L-1. Three sprint TTL patterns were identified: a pattern with two long ~14‒15-week macrocycles, one with two ~12‒13 week macrocycles each composed of a balanced training load, and one with a single stable flat macrocycle. The long pattern elicited the fastest performances and was most prevalent in Olympic quadrennials (i.e., 4 seasons preceding the 2004, 2008 and 2012 Olympic Games). This pattern exhibited moderate week-to-week TTL variability (6±3%), progressive training load increases between macrocycles, and more training at ≤4 mmol.L-1 and >6 mmol.L-1. This fastest sprint pattern showed a waveform in the second macrocycle consisting of two progressive load peaks 10‒11 and 4‒5‒6 weeks before competition. The stable flat pattern was the slowest and showed low TTL variability (4±3%), training load decreases between macrocycles (P<0.01), and more training at 4‒6 mmol.L-1 (P<0.01). Conclusion: Progressive increases in training load, macrocycles lasting about 14‒15 weeks, and substantial volume of training at intensities ≤4 mmol.L-1 and >6 mmol.L-1, were associated with peak performance in elite swimmers.